Human rights institute under english law - A. A. Otynshiyeva; Zh. T. Sairambayeva; Z. M. Baimagambetova; L. B. Nyssanbekova; J. Castellino (Хабаршы. Заң сериясы, 2022)
The article examines the human rights issues, especially citizenship institute based on the experience the United Kingdom. An analysis of the scientific views of domestic and foreign scientists; reveals the problematic aspects of protecting human rights institute. In the era of globalization, the role of the human rights in solving urgent problems of human civilization is growing. In recent years, dramatic changes have occurred in the global legal system and the legal system of the UK. These changes will serve as the basis for the protection, enforcement and development of human rights. On the one hand, it is a process of integration and regionalization based on world globalization; on the other hand, domestic political and liberal reform processes in the UK. The main focus of the article is to study the legal status of individuals in the UK in the context of globalization, to develop proposals for improving the legislation on human rights in the Republic of Kazakhstan. The article provides for the disclosure of the legal status of the individual through global processes and author's interpretation of it, the legal basis for the protection of human rights, the definition of the features of the formation of human and civil rights and freedoms in the UK, proposals were made for its further development in Kazakhstan.